A CASE REPORT OF 41-YEAR-OLD MALE WITH POST TRAUMATIC ENCEPHALOMALACIA - Fathia Kharitano; Feda Anisah Makkiyah (The SDGS Forum Communication, 2026)
Encephalomalacia is the softening of brain tissue resulting from hemorrhagic contusions, infarctions, or diffuse axonal injury, which can develop months or even years after head trauma. Encephalomalacia may occur in adults, albeit rarely, following acquired brain injuries such as infection, trauma, or infarction. We report a 41-year-old male who presented with headache and memory loss, symptoms that developed one year after a motorcycle accident in which he sustained a head injury. Imaging revealed hypodense lesions in the left temporoparietal lobe, consistent with encephalomalacia and associated ventriculomegaly. This case highlights the significance of detailed clinical and radiological assessments in diagnosing encephalomalacia, underscoring the importance of early intervention and management to prevent long-term neurological complications.